2019
DOI: 10.4102/sajim.v21i1.1026
|View full text |Cite
|
Sign up to set email alerts
|

Use of electronic resources by students in a premier postgraduate theological university in Ghana

Abstract: The use of e-resources, a prevalent phenomenon in universities, is crucial as it enables the enhancement of academic work (Deng 2010:97). The need arises, therefore for postgraduate students, whose studies focus on the conduct of research, to maximise the use of e-resources in their studies. While some studies in Ghana (Borteye & Dadzie 2015; Kwadzo 2015), Nigeria (Akporhonor & Akpojotor 2016) and Uganda (Okello-Obura 2010), for example, have investigated e-resource utilisation among postgraduate students, e-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…In a related study on use of electronic information resources among the students and researchers of Faculty of Arts by Thanuskodi (2012), it was revealed that majority of the respondents used electronic resources for various purposes such as writing papers, studying, research purpose, updating knowledge and for examination. In a separate study in Ghana, Akuffo (2019) and Ankrah & Acheampong (2017) revealed that students use electronic resources for research and assignments. However, Daramola (2016) reported low use of electronic resources among undergraduates in the Federal University of Technology, Akure, Nigeria while Ajibili (2013), Mawere & Sai (2018) made same conclusion in similar studies conducted in Zimbabwe and Bingham respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a related study on use of electronic information resources among the students and researchers of Faculty of Arts by Thanuskodi (2012), it was revealed that majority of the respondents used electronic resources for various purposes such as writing papers, studying, research purpose, updating knowledge and for examination. In a separate study in Ghana, Akuffo (2019) and Ankrah & Acheampong (2017) revealed that students use electronic resources for research and assignments. However, Daramola (2016) reported low use of electronic resources among undergraduates in the Federal University of Technology, Akure, Nigeria while Ajibili (2013), Mawere & Sai (2018) made same conclusion in similar studies conducted in Zimbabwe and Bingham respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Mawere and Sai (2018) define electronic resources or sometimes refers to as electronic information resources as the collections of information in electronic or digital format that are accessed on an electronic device, such as a mobile phone, computer, etc. In the Work of Akuffo and Budu (2019), electronic resources is also refers to as electronic information storage systems accessed via electronic systems and computer networks. Electronic resources or electronic information resources is also refers to as any materials or resources that need access either remotely (via the Internet using a personal computer or mainframe or handheld mobile device) or locally (IFLA; 2012).…”
Section: Background To the Studymentioning
confidence: 99%
“…As the utilization of electronic assets is as yet a state of conversation for some researchers, they have concentrated on the benefits and impediments of these assets and how the understudies utilize these assets. Singh2013, Dattatraya andet al 2013, Tlakula andFombad (2017) (Akuffo & Budu 2019, Mehla 2018, Sharma. 2019, Toyo 2017.…”
Section: Review Of the Related Studiesmentioning
confidence: 99%
“…It additionally showed that the degree of mindfulness and preparation in the utilization of these assets is fundamental. A review led by Akuffo & Budu (2019) inspected 33 postgraduate understudies' degree of familiarity with e-assets, how they access and use eassets, the reasons for using e-assets, and the upsides of and challenges in using e-assets. The review showed high mindfulness levels, sufficient PC abilities, various benefits, use of e-assets for scholastic uses, and inadequate pursuit abilities of most understudies because of the absence of preparation.…”
Section: Review Of the Related Studiesmentioning
confidence: 99%